1991
DOI: 10.1007/bf01310474
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1vif, vpr, andvpu mutants can produce persistently infected cells

Abstract: A series of human immunodeficiency virus type 1 (HIV-1) mutants in vif, vpr, vpu, and nef were constructed from an infectious plasmid (pNL 432) containing the full-length HIV-1 DNA by frameshift mutations. The capacities for replication and cell killing of these mutant viruses were examined in a clonal cell line (M 10) isolated from HTLV-I-transformed MT-4 cells. In all cases, the mutant viruses replicated, expressed HIV-1 antigens, and induced drastic cytopathic effects. However, some M 10 cells survived infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…Our recent results show that more extensive mutations in this region, including a large deletion of the v~f to vpr region, predominate within persistently infected cultures derived from further serial passage of wild-type HIV-1 (T. Nakaya et al, unpublished results). These observations are in keeping with our previous findings that HIV-1 with mutations in the accessory genes vif, vpr or vpu lead to the generation of persistent infections in M10 cells (Nishino et al, 1991 ;Kishi et al, 1992Kishi et al, , 1993. Moreover, these results imply that accessory gene products modulate the maturation and/or expression of Env proteins, as these are the eventual effectors of cell killing by their interaction with the CD4 receptor molecule (Koga et al, 1990).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our recent results show that more extensive mutations in this region, including a large deletion of the v~f to vpr region, predominate within persistently infected cultures derived from further serial passage of wild-type HIV-1 (T. Nakaya et al, unpublished results). These observations are in keeping with our previous findings that HIV-1 with mutations in the accessory genes vif, vpr or vpu lead to the generation of persistent infections in M10 cells (Nishino et al, 1991 ;Kishi et al, 1992Kishi et al, , 1993. Moreover, these results imply that accessory gene products modulate the maturation and/or expression of Env proteins, as these are the eventual effectors of cell killing by their interaction with the CD4 receptor molecule (Koga et al, 1990).…”
Section: Discussionsupporting
confidence: 80%
“…We previously reported that HIV-1 with mutations in accessory genes, such as vif, vpr or vpu, could generate persistent infections in M10 cells (Nishino et al, 1991;Kishi et al, 1992Kishi et al, , 1993. Thus, mutations in these accessory genes might contribute to the generation of persistent infections by serial passage of wild-type HIV-1.…”
Section: Nef--i [Nef -I(a)] Nef-lo [Nef-lo(a)] or Nef -50 [Nef--50(a)]mentioning
confidence: 99%
“…The HIV-1 accessory protein viral protein R (Vpr) is an important determinant of viral cytopathicity and can independently kill cells in the absence of viral infection (45,55,60).…”
Section: Human Immunodeficiency Virus Type 1 (Hiv-1) Infection Is Chamentioning
confidence: 99%
“…An attractive possibility is that replacements in gag could have multiple effects in RNA-protein interactions, nucleocapsid assembly, and protein stability (16,30) and that such effects could contribute to fitness loss. It must also be considered that Vif, Vpr, and Nef are dispensable functions for HIV-1 replication in some permissive cell lines, including MT-4 (7,49). Therefore, the accumulation of nonsynonymous replacements in vif, vpr, and nef genes (Fig.…”
Section: Vol 74 2000 Mutations and Bottlenecks In Hiv-1 9549mentioning
confidence: 99%